Sejarah Perkembangan Kekuasaan Kehakiman di Indonesia - Ridham Priskap (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Judicial power in Indonesia from the past until now still exists despite the ups and downs, the history of the development of this institution has begun long before independence, even before the Dutch East Indies were entrenched in the archipelago, this judicial authority has existed in the form of traditional justice institutions. As an institution that provides protection to the community, the judicial authority has shown its functions as the last stronghold to seek legal justice for the community.